2016
DOI: 10.5709/acp-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the Visual Processing of Viewing Complex Visual Stimuli Amongst Individuals With Body Image Concern

Abstract: Individuals with body dysmorphic disorder (BDD) and clinically concerning body-image concern (BIC) appear to possess abnormalities in the way they perceive visual information in the form of a bias towards local visual processing. As inversion interrupts normal global processing, forcing individuals to process locally, an upright-inverted stimulus discrimination task was used to investigate this phenomenon. We examined whether individuals with nonclinical, yet high levels of BIC would show signs of this bias, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 59 publications
4
11
1
Order By: Relevance
“…Consistent with previous similar studies [ 6 , 37 ], the dimensions for all images on screen were 15 X 12 degrees of visual angle (height x width). The behavioral task ran on an IBM compatible PC and the software Presentation [ 46 ] was used to present stimuli and record reaction time (RT) and accuracy for discrimination between pairs of stimuli.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with previous similar studies [ 6 , 37 ], the dimensions for all images on screen were 15 X 12 degrees of visual angle (height x width). The behavioral task ran on an IBM compatible PC and the software Presentation [ 46 ] was used to present stimuli and record reaction time (RT) and accuracy for discrimination between pairs of stimuli.…”
Section: Methodssupporting
confidence: 89%
“…Conversely, some research [ 37 38 ] has challenged the presence of a local processing bias in those with BDD and/or high BIC. For example, Monzani [ 38 ] used a number of measures, including the face inversion task, to demonstrate that visual processing of those with BDD did not differ from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that in addition to impairment of facial recognition, this sample also presented impairment in the recognition of faceless body silhouette stimuli. Similarly, Duncum et al (2016) presented body stimuli, objects and scenes for 500 ms to a group of body image concern participants. The set of stimuli were randomly presented in regular and inverted orientation.…”
Section: Introductionmentioning
confidence: 99%